USING DICTATION METHOD IN TEACHING ENGLISH LISTENING SKILL AT SEVENTH GRADE STUDENTS OF MTS 1 PAB HELVETIA - Aslamiah, Aslamiah (Faculty of Tarbiyah nad Teacher Training, 2023)
The research is aimed to find out the following question: Is the students’ listening skill taught by using Dictation Method better than without Dictation Method. The sample of this research were two classes, such as 30 students at VII C as experimental class and 30 students VII D as control class VII MTs PAB 1 Helvetia for the 2020/2021. The finding research shows that: Dictation Method prove that using it can make better score in conducting test, especially in listening skill. It looks from their score. The analysis of the test used normality and homogeneity test, and analyzing the data used t-test formula. After that, the writer do; (1) the students listening skill by using dictation method got the meant 73,16 and standard deviation is 12,55. (2) the students listening skill without dictation method got the mean 65 and standard deviation is 12,86, The t-test results also show that t(observed) 2,45 is higher than t(table) at a significance level of 5% (0.05) with 58 degrees of freedom of 2.045. From the results of 2,45> 2.045 result in H0 (null hypothesis) rejected and Ha (alternative hypothesis) accepted. So that, the alternative hypothesis (Ha) proposed is accepted and null (Ho) is rejected. So it can be conclude that there is better of using dictation method in listening skill.